(untitled) (Journal of Information Technology and Digital World, 2022)
Human activity monitoring system plays a major role in the application of surveillance. It can be analyzed through cameras, sensors, and microphone. The traditional approach requires a human intervention for validating the human movement recorded by a surveillance camera and microphone. Therefore, the sensor based approaches are developed to make an alert signal through a buzzer or light, irrespective of the threshold value given to its output. But such sensor based technique also requires a human attention in the monitoring room. The motive of the proposed concept is to address such limitations by connecting the sensors with an Internet of Things (IoT) network and cloud platform for remote recording and monitoring purposes. The proposed work utilizes the Blynk IoT application and cloud server for the analytics.